Understanding the Effects of Naturalistic Developmental Behavioral Interventions: A Project AIM Meta‐analysis. Issue 4 (22nd January 2021) - Crank, Jenna E.; Sandbank, Micheal; Dunham, Kacie; Crowley, Shannon; Bottema‐Beutel, Kristen; Feldman, Jacob; Woynaroski, Tiffany G.
Abstract: We examined the quality of evidence supporting the effects of Naturalistic Developmental Behavioral Interventions (NBDIs) for facilitating change in young children with autism. We also investigated whether effects varied as a function of specific features of the intervention, samples, and outcomes measured. Twenty‐seven studies testing the effects of NDBIs were extracted from data collected for the A utism I ntervention M eta‐analysis (Project AIM), a comprehensive meta‐analysis of group design, nonpharmacological intervention studies for children with autism aged 0–8 years. We extracted effect sizes for 454 outcomes from these studies for use in meta‐regression analyses testing associations between intervention effects and mean participant chronological age, language age, autism symptomatology, percentage of sample reported as male, cumulative intervention intensity, interventionist, outcome boundedness, outcome proximity, and risk of parent/teacher training correlated measurement error. The extant literature on NDBIs documents effects on social communication, language, play, and cognitive outcomes. However, our confidence in the positive and significant summary effects for these domains is somewhat limited by methodological concerns. Intervention effects were larger for context‐bound outcomes (relative to generalized), and for proximal outcomes (relative to distal). Our results indicate that NDBIs have promise as an approach for supporting development for some, but not all of the core and related features of autism in early childhood. Confidence in summary effect estimates is limited by study quality concerns, particularly an overreliance on measures subject to high detection bias. The results of this review support the use of proximity and boundedness as indicators of the limits of intervention effects. Lay summary: Naturalistic Developmental Behavioral Interventions may increase language, social communication, play skills, and cognition in young children with autism, but these increases are largest for skills directly targeted by the intervention, and in contexts that are similar to that of the intervention. These conclusions are tempered by some concerns regarding research design across the studies that have been conducted to date. Autism Res 2021, 14: 817–834 . © 2021 International Society for Autism Research and Wiley Periodicals LLC